2020
DOI: 10.1021/acsomega.0c02642
|View full text |Cite
|
Sign up to set email alerts
|

Development and Performance Evaluation of a High-Temperature Profile Control System

Abstract: In the late stage of the steam flooding development of heavy oil reservoirs, the contradiction between layers is prominent, which makes the development of the reservoir difficult. To obtain a profile control agent suitable for steam flooding in heavy oil reservoirs, the modification technology was used to improve the temperature resistance of the traditional NH-1 main agent, as the conjugation effect may enhance the stability of the molecular structure. Thus, we obtained the modified NH-1 main agent, which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Similar studies of the use of hydrogels for leveling the inflow profile under conditions of steam treatment were carried out in the work [ 176 ] where a high-molecular organic polymer was modified by the addition of graphite nanoparticles. Studies showed an increase in the blocking ability of the gel when graphite particles are added.…”
Section: Gels For Water and Gas Shutoffmentioning
confidence: 78%
“…Similar studies of the use of hydrogels for leveling the inflow profile under conditions of steam treatment were carried out in the work [ 176 ] where a high-molecular organic polymer was modified by the addition of graphite nanoparticles. Studies showed an increase in the blocking ability of the gel when graphite particles are added.…”
Section: Gels For Water and Gas Shutoffmentioning
confidence: 78%
“…However, the hexagonal pores were not observed in the microstructure of the PAM-GO gel system, which may be related to the hydrophilicity of GO particles. Wang et al (2020) prepared a graphite-enhanced gel system with polymer NH-1, crosslinking agents I and II, graphite particles, and suspension concentrate carboxymethyl cellulose (CMC); however, the precise crosslinker formula was not provided. The viscosity of the graphite-enhanced gel system reached 430,000 mPa s at 200 °C.…”
Section: Graphite-enhanced Gel Systemmentioning
confidence: 99%
“…Therefore, it is necessary to develop new additives to improve the performance of polymer gel. In recent years, graphite materials have attracted much attention as a hot topic in the field of micro-materials [25][26][27][28][29]. The modified hydrophilic micron graphite powder has a layered structure with abundant hydroxyl and carboxyl functional groups on its surface, so it can be uniformly dispersed in water.…”
Section: Introductionmentioning
confidence: 99%